Learning and Affect Following Near‐Miss Outcomes in Simulated Gambling. (12th November 2012) - Clark, Luke; Liu, Rui; McKavanagh, Rebecca; Garrett, Alice; Dunn, Barnaby D.; Aitken, Michael R. F.
ABSTRACT Gambling near‐misses are non‐rewarded events that resemble a winning configuration. Past research using slot machines has shown that moderate rates of near‐misses increase gambling persistence, but the mechanisms supporting this persistence are unclear. One hypothesis is that near‐misses are mistakenly interpreted as signals of skill acquisition, supporting learning and fuelling the 'illusion of control'. A slot machine simulation was administered to 60 volunteers, with ratings of the perceived chances of winning, pleasure and motivation to play following particular outcomes. Psychophysiological measures (electrodermal activity and heart rate) were taken, and gambling persistence was measured after 30 trials. Near‐misses were similar to full‐miss outcomes in that they were regarded as unpleasant. However, near‐misses were akin to win outcomes in that they increased motivations to play and electrodermal activity. Learning was evidenced by the expectancy of winning increasing following wins and decreasing after losses. Although there was no overall change in expectancy of winning after near‐misses across all participants, those subjects reporting a greater increase in the expectancy of winning following a near‐miss showed more persistent play, consistent with the learning hypothesis. Greater heart rate acceleration following near‐misses was also associated with persistence. We also observed differential effects of near‐misses where the reel stopped either side of the winning position ('payline'): motivational effects were restricted to near‐misses stopping before the payline, whereas near‐misses that stopped after the payline were primarily aversive. The payline effects are not predicted by the learning hypothesis and may indicate an affective component to near‐misses, possibly linked to counterfactual processing. Copyright © 2012 John Wiley & Sons, Ltd.